An Examination of Whether and How Racial and Gender Biases Influence Customer Satisfaction - Hekman, David R.; Aquino, Karl; Owens, Bradley P.; Mitchell, Terence R.; Schilpzand, Pauline; Leavitt, Keith (Academy of Management Journal, 2010)
We examined whether and how various biases may influence customers' satisfaction evaluations and produce discriminatory judgments for minority and female service employees. We argue that customer satisfaction evaluations are biased because they are anonymous judgments by untrained raters that usually lack an evaluation standard. Laboratory and field samples provide disturbing evidence generally confirming our arguments and suggesting that the presence of nonwhite and women service employees may produce lower aggregated customer satisfaction evaluations that may ultimately hurt individuals and organizations financially.